2011
DOI: 10.1590/s0101-60832011000400008
|View full text |Cite
|
Sign up to set email alerts
|

Potenciais biomarcadores da terapia cognitivo-comportamental para o transtorno de estresse pós-traumático: uma revisão sistemática

Abstract: Background: The establishment of biomarkers related to cognitive-behavior therapy (CBT) is a method to objectively consolidate treatment efficacy, which is critical to advancing the field. Objectives: We systematically reviewed studies that used biological parameters to assess the efficacy of CBT for the treatment of post-traumatic stress disorder (PTSD) and studies that used these parameters as predictors of response to CBT. Methods: Computerized literature searches were conducted in PubMed/Medline, ISI/Thomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(43 reference statements)
1
3
0
3
Order By: Relevance
“…Gonçalves et al (2011) investigated potential CBT biomarkers of efficacy in the treatment of PTSD and found results consistent with this meta-analysis regarding heart rate. In a recent systematic review (Zantvoord et al, 2013), also in patients with PTSD, reduced physiological reactivity was found in line with the decrease in symptoms after treatment with CBT.…”
Section: General Resultssupporting
confidence: 61%
“…Gonçalves et al (2011) investigated potential CBT biomarkers of efficacy in the treatment of PTSD and found results consistent with this meta-analysis regarding heart rate. In a recent systematic review (Zantvoord et al, 2013), also in patients with PTSD, reduced physiological reactivity was found in line with the decrease in symptoms after treatment with CBT.…”
Section: General Resultssupporting
confidence: 61%
“…Between the first and second assessment, the treatment and intervention for PTSD was conducted using Cognitive Behavioral Therapy (CBT) twice per week for a period of 12 months. Cognitive Behavioral Therapy has been considered a resource of choice for the treatment of PTSD (Gonçalves et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Beyond pharmacological treatment, it is possible to observe increases in this neurotrophin's levels via electroconvulsive therapy (13) and physical activity (14) concurrent to the remission of psychological symptoms. Previous reviews of psychotherapies showed few potential response biomarkers for this treatment in patients diagnosed with PTSD such as the 5-alfa-reductase, heart rate changes (15), glucocorticoid metabolism, gene methylation, (16) and structural brain changes (17).…”
Section: Introductionmentioning
confidence: 99%